Perbedaan Kekasaran Permukaan Gic Tanpa dan Dengan Penambahan Kitosan Setelah Perendaman Minuman Isotonik - Iin Sundari (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
Conventional glass ionomer cement (GIC) is an aesthetic dental restoration materials that still used nowadays due to its own advantage, particularly the ability of GIC to release fluoride as anticariogenic. GIC restoration materials have low mechanical properties and low erossion resistance so GIC was modified by adding chitosan. The purpose of this research is to know the difference of surface roughness GIC without and with the addition of Chitosan after immersion in isotonic drink. There were 20 specimen that consists of two groups of treatment. The first group used conventional GIC and the second group used the GIC with the addition of Chitosan 10% v/v. All specimen cylindrical shapes with a diameter of 10 mm and a thickness of 2 mm. Both groups were kept immersed in isotonic drink for 24 hours. Surface roughness after immersion were measured using surface roughness tester TR200. Independent t-test results showed no meaningful difference (p>0.05) between conventional GIC (1,33 ± 0,34) and GIC with the addition of Chitosan 10% v/v (1,10 ± 0,29) after immersion. It can be concluded that the addition of Chitosan 10% v/v could decrease surface roughness of GIC although no meaningful difference.